A retrospective matched-pair analysis of long-term outcomes after successful lower extremity free flap salvage - Bigdeli, Amir Khosrow; Strübing, Felix; Troia, Roman; Thomas, Benjamin; Gazyakan, Emre; Kneser, Ulrich; Hirche, Christoph (Journal of reconstructive microsurgery, 2023)
Background: Pedicle occlusion with total free flap loss after microvascular lower extremity reconstruction is a considerably rare yet devastating complication. Fortunately, in the majority of cases, emergency salvage takebacks of compromised free flaps are initiated in a timely manner. In this report, we present our analysis of long-term outcomes following transient vascular compromise mitigated through successful free flap salvage in the lower extremity. Methods: We performed a single-center retrospective matched-pair analysis of 46 patients with lower extremity free flap reconstructions. Cases underwent successful revisions of microvascular compromise (n = 23), whereas controls had uneventful postoperative courses (n = 23). Patient-reported outcome questionnaires and physical evaluations were used to assess general quality of life, functional outcomes, and cosmesis (Lower Extremity Functional Scale [LEFS], Lower Limb Outcomes Questionnaire [LLOQ], Short Form 36 (SF-36), Vancouver Scar Scale [VSS]). The mean follow-up time was 4.4 years. Results: The health-related quality of life assessed by the SF-36 did not differ significantly between both groups in any of the subscales (p ≥ 0.15 for all subscales). Functional outcomes did not show significant differences between both groups according to the LEFS (p = 0.78) and LLOQ (p = 0.45). The overall scar appearance assessed by the VSS showed significantly poorer cosmesis in the re-exploration group (p = 0.014). Conclusion: Salvage of compromised free flaps in the lower extremity yields similar long-term outcomes compared to noncompromised free flaps with regard to function and quality of life. However, free flap revisions may lead to impaired scar formation. This study provides further evidence that the opportunity for urgent re-exploration is indispensable.